1992
DOI: 10.1128/mcb.12.8.3583
|View full text |Cite
|
Sign up to set email alerts
|

pp39mos is associated with p34cdc2 kinase in c-mosxe-transformed NIH 3T3 cells.

Abstract: We investigated the possible interactions between pp39mos and p34cdc2 kinase in NIH 3T3 cells transformed by c-mosxe. pp39mos is coprecipitated with p34cdc2 when using either anti-PSTAIR antibody or p13suc1-Sepharose beads. Likewise, p34cdc2 is coprecipitated with pp39mos when using anti-mos antibody. However, pp39mos was not present in histone H1 kinase-active p34cdc2 complexes precipitated with anti-p34cdc2 C-terminal peptide antibody even during metaphase of the cell cycle. The molar ratio of p34 to pp39mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In this study, we further demonstrate from the GST pull-down assay that CagSpin directly or indirectly associates with h-tubulin, and therefore provide the first biochemical evidence for the specific interaction of Spindlin protein and h-tubulin, the microtubule component. Interestingly, some important proteins that play crucial functions during oocyte maturation and egg fertilization, such as p39 mos (Zhou et al, 1992;Haccard et al, 1993;Verlhac et al, 1996), p34 cdc2 of metaphase promoting factor (MPF) (Langan et al, 1989;Peter et al, 1990;Verde et al, 1990;Zhou et al, 1991Zhou et al, , 1992, cyclin B, the regulatory component of MPF (Pines and Hunter, 1991;Ookata et al, 1993), MAP kinase (Verlhac et al, 1993) and PKC (Page Baluch et al, 2004), have been also confirmed to associate with microtubules. Interestingly, three putative PKC phosphorylation sites have been revealed in the CagSpin sequence (Fig.…”
Section: Biochemical Evidence Of Association Between B-tubulin and Camentioning
confidence: 99%
“…In this study, we further demonstrate from the GST pull-down assay that CagSpin directly or indirectly associates with h-tubulin, and therefore provide the first biochemical evidence for the specific interaction of Spindlin protein and h-tubulin, the microtubule component. Interestingly, some important proteins that play crucial functions during oocyte maturation and egg fertilization, such as p39 mos (Zhou et al, 1992;Haccard et al, 1993;Verlhac et al, 1996), p34 cdc2 of metaphase promoting factor (MPF) (Langan et al, 1989;Peter et al, 1990;Verde et al, 1990;Zhou et al, 1991Zhou et al, , 1992, cyclin B, the regulatory component of MPF (Pines and Hunter, 1991;Ookata et al, 1993), MAP kinase (Verlhac et al, 1993) and PKC (Page Baluch et al, 2004), have been also confirmed to associate with microtubules. Interestingly, three putative PKC phosphorylation sites have been revealed in the CagSpin sequence (Fig.…”
Section: Biochemical Evidence Of Association Between B-tubulin and Camentioning
confidence: 99%
“…The washed pellets were resolved by SDS-PAGE and transferred to nitrocellulose filters. The lanes corresponding to the unlabelled proteins were immunoblotted with either ␣-or ␤-tubulin antibody, while the lanes corresponding to the 35 Slabelled lysate were exposed directly to autoradiography. We observed that the two predominant bands precipitated when the GST-Myc II was incubated with 35 S-labelled extracts comigrated with ␣-and ␤-tubulins (Fig.…”
Section: Specific Binding Of C-myc To Tubulin In Vitromentioning
confidence: 99%
“…Although several cMos-interacting proteins have been described (Zhou et al, 1991a(Zhou et al, , 1992Bai et al, 1992aBai et al, ,b, 1993Cooper, 1995, 1997;Chen et al, 1997), which help to explain the basis of c-Mos function in oocyte maturation and cellular transformation, regulation of c-Mos activity is still poorly understood. In this study we provide evidence that Hsp70 molecular chaperone is a major Mos-associated protein.…”
Section: Introductionmentioning
confidence: 99%